Influence of transverse rebars on bond between steel reinforcement and cellular concrete with very low compressive strength - Soudais, P. R. N.; Camacho, J. S.; Parsekian, G. A. (IBRACON - Instituto Brasileiro do Concreto, 2018)
Abstract Cellular concrete is a lightweight concrete obtained by aerating agent, which produces air-voids into the mixture. This work deals with bond between cellular concrete and steel rebars. Pull-out tests of 4,2 mm diameter rebars partly immersed into concrete cylinders were made. Concrete unit weight variation and setting of a transverse rebar into the concrete cylinder center constitute the variables of the work. Three types of mixture were prepared: one without aerating agent (with a dry unit weight of 2255 kg/m3), and two with different aerating agent rates (with a dry unit weight equal to 1565 and 1510 kg/m3). The study revealed the large decrease of bond stress between 4,2 diameter rebars and cellular concrete, due to concrete unit weight reduction. Transverse rebar introduced into concrete cylinder center increased the ultimate pull-out force of the test: the gain of bond produced by the transverse rebar grew up when the cellular concrete unit weight had been reduced. Therefore, special anchorages (not exclusively straight), permitting bond improvement between cellular concrete and rebars could be a solution to improve the mechanical performance of cellular concrete.

Resumo O concreto celular, que se caracteriza por ter um peso próprio reduzido pela incorporação artificial de ar, pode constituir uma alternativa sustentável ao concreto comum nas estruturas de pequeno e médio porte. O presente trabalho trata da avaliação da aderência entre o concreto celular e as barras de aço. Foram realizados ensaios de arrancamento com barras de diâmetro igual a 4,2 mm, parcialmente imersas em corpos-de-prova cilíndricos de concreto. A taxa de agente espumígeno no concreto e a presença ou não de uma barra transversal dentro do cilindro, simulando uma condição mais próxima ao uso de tela de aço, constituem as variáveis da pesquisa. Foram utilizadas três dosagens de concreto, com massa específica aparente de 2255, 1565 e 1510 kg/m3. Pelo arrancamento de barras simples de diâmetro igual a 4,2 mm, notou-se o forte decréscimo da tensão de aderência junto com o rebaixamento da massa específica aparente do concreto. A barra transversal permitiu obter um ganho de resistência ao arrancamento da barra longitudinal, que cresceu junto com o rebaixamento da massa específica do concreto celular. Assim, a utilização de ancoragens especiais (não exclusivamente retas), pode se tornar uma solução para melhorar o desempenho mecânico do concreto celular.
Influência do uso de barras transversais soldadas na aderência aço-concreto celular de baixíssima resistência à compressão
Keywords: cellular concrete; bond stress; anchoring.; concreto celular; aderência; ancoragem